This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
nice logic
n 2 + 2 n + 1 = ( n + 1 ) 2 2 n + 1 = 3 1 , n = 1 5 , n + 1 = 1 6 if in a math similar to this, ( n + 1 ) 2 doesn 't work, use n 2 + 4 n + 4 = ( n + 2 ) 2 and so on......
Problem Loading...
Note Loading...
Set Loading...
( x + y ) ( x − y ) = 3 1 and 3 1 is a prime number, so x + y = 3 1 and x − y = 1 , which means that x = 1 6 and y = 1 5 . And then it's simple.